2010
DOI: 10.1042/bj20100166
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphoinositide 3-kinase β in platelet aggregation and thromboxane A2 generation mediated by Gi signalling pathways

Abstract: PI3Ks (phosphoinositide 3-kinases) play a critical role in platelet functional responses. PI3Ks are activated upon P2Y12 receptor stimulation and generate pro-aggregatory signals. P2Y12 receptor has been shown to play a key role in the platelet aggregation and thromboxane A2 generation caused by co-stimulation with Gq or Gz, or super-stimulation of Gi pathways. In the present study, we evaluated the role of specific PI3K isoforms alpha, beta, gamma and delta in platelet aggregation, thromboxane A2 generation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…PI3Kb mediates GPCR receptor signaling, regulating thrombinand ADP-mediated platelet aggregation (13,14), as well as LPA receptor-mediated signals via the small GTPase rac (15). Consistent with this, AZD8186 inhibits ADP-induced human platelet aggregation with a mean IC 50 value of 186 nmol/L (Fig.…”
Section: Resultssupporting
confidence: 56%
“…PI3Kb mediates GPCR receptor signaling, regulating thrombinand ADP-mediated platelet aggregation (13,14), as well as LPA receptor-mediated signals via the small GTPase rac (15). Consistent with this, AZD8186 inhibits ADP-induced human platelet aggregation with a mean IC 50 value of 186 nmol/L (Fig.…”
Section: Resultssupporting
confidence: 56%
“…PI 3-kinase ␤ has been shown to play an important role in signaling downstream of ␣IIb␤3 (44), and our work has shown that PI 3-kinase ␤ plays an important role in ADP-induced TxA 2 generation (45). Thus, it is possible that Pyk2 mediates ADP-induced TxA 2 generation by regulating PI 3-kinase ␤ activity in platelets.…”
Section: Discussionmentioning
confidence: 74%
“…Platelet granule release is potentiated by P2Y 12 receptor stimulation (Dangelmaier et al, 2001;Garcia et al, 2010). The P2Y 12 receptor gene variants correlate with pulmonary inflammation and asthma (Bunyavanich et al, 2012), and receptor deficiency abrogated dust mite-induced airway inflammation (Paruchuri et al, 2009), suggesting an important role for the P2Y 12 receptor in pulmonary inflammation.…”
Section: Introductionmentioning
confidence: 99%